EDUKASI LINGKUNGAN HIJAU BERBASIS ISLAMI PADA MASYARAKAT DI KALURAHAN KALIANCAR, SELOGIRI, WONOGIRI, JAWATENGAH - Agus Fatuh Widoyo; Siti Fathiyatus Sholihah; Batul Rizka; Ibni Nur Salamah; Najmudin Zaky (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
Environmental issues are crucial issues that directly impact people's quality of life. Issues such as waste accumulation, poor environmental hygiene, and minimal ecological awareness demonstrate that environmental damage is not only caused by technical factors, but also by weak community values ​​and behavior. This community service activity aims to increase community awareness and participation in environmental protection through an Islamic da'wah approach. Therefore, researchers conducted a socialization program in Kaliancar Village, Wonogiri. The program, which was held on Sunday, January 18, 2026, attracted 45 participants, consisting of 20 men and 25 women, at the Al Amin Mosque in Kaliancar. The program included lectures, practical activities in sorting organic and inorganic waste, and a question-and-answer session. After this socialization is carried out, participants are expected to be able to preserve the surrounding environment by managing waste by sorting organic and inorganic waste, such as plastic. Plastic can be reprocessed into new useful products. In addition, the community can preserve the environment by planting oxygen-producing plants.